2012
DOI: 10.4028/www.scientific.net/amr.488-489.1147
|View full text |Cite
|
Sign up to set email alerts
|

Six Sigma DMAIC Methodology: A Powerful Tool for Improving Business Operations

Abstract: Six Sigma is a popular approach to drive out variability from processes using powerful statistical tools and technique. Six Sigma permits only 3.4 defects per million opportunities. Six Sigma follows basics methodology to improve existing process, i.e. DMAIC. Define, Measure, Analyze, Improve, Control. It is , scientific, systematic and fact based approach. This paper also includes various applications of DMAIC methodology in different business sector like Electronics sector, Chemical and Agriculture manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Moving on, during the Improve phase solutions were created and implemented [26]. Creative, cheaper, and faster solutions are preferred from a Lean perspective [27].…”
Section: Methodsmentioning
confidence: 99%
“…Moving on, during the Improve phase solutions were created and implemented [26]. Creative, cheaper, and faster solutions are preferred from a Lean perspective [27].…”
Section: Methodsmentioning
confidence: 99%
“…Su and Chou (2008) considered Six Sigma as a structured process improvement methodology by means of the DMAIC (Define, Measure, Analyse, Improve and Control) process in combination with a well-defined set of tools. The DMAIC is a process of continuous improvement (Kumar and Sharma, 2012) of five phases: definition, measurement, analysis, improvement and control. This methodology has been used in several studies aimed at improving processes, such as the studies reported by Kumaravadivel and Natarajan (2013); Srinivasan et al (2014a, 2014b); Nithyanandam and Pezhinkattil (2014).…”
Section: Introductionmentioning
confidence: 99%